New Public Governance methods in EU health policy formation - Białynicki-Birula, Paweł (Journal of Public Governance, 2012)
The aim of the article is to present the perspectives of development of EU health policy, including its potential impact on health policy of the Member States. Due to the existing treaty limitations and increasing complexity of relationships in the area of health policy, the role of the so-called soft forms of coordination (soft law), which are the instruments of the new public governance, in the process of expanding the European competences seems to become more and more signifi cant. Therefore, particular attention has been paid to two specific institutional solutions which are of crucial importance to the development of European health policy: to the open method of co-ordination, and to regulatory agencies. Methods of new public governance could fill gaps in the formal EU competences and be seen as a way of gradually broadening the scope of the Community’s “interest” in health issues. Th e growing role of the EU in the domain of health is consistent with the general pattern of the Member States’ declining sovereignty over the social sphere. However, one should not assume that they will lose their influence over health and social benefits any time soon. Social policy and redistribution is in fact crucial for nation-state legitimacy. Thus, in the short term, we should rather expect that the process of negative integration is going to continue, that the judicial decisions of the ECJ are going to keep playing the destabilizing role, and that public governance methods in the area of health policy are going to be developed further.